Inovasi dan Tradisi: Analisis Perbandingan Metode Pembelajaran PAI di Sekolah Dasar/MI Indonesia dan Brunei Darussalam - I.M. Fatimah Zahro; Sukardi, Ismail; Astuti, Mardiah; Fikri, Aiman; Bahrudin, Andre (TAUJIH: Jurnal Pendidikan Islam, 2024)
This study compares Islamic Religious Education (PAI) teaching methods in Indonesia and Brunei Darussalam, focusing on the aspects of innovation and tradition. The aim is to analyze how innovative and traditional methods affect students' understanding, as well as the challenges faced by teachers in their implementation. Using the Systematic Literature Review (SLR) method, this research compiles data from literature related to PAI education in both countries. The findings reveal significant differences between PAI teaching methods in Indonesia and Brunei Darussalam, particularly in the aspects of innovation and tradition. In Indonesia, the use of innovative methods such as technology-based and project-based learning shows increased student engagement, although learning outcomes remain inconsistent due to challenges like teacher readiness and infrastructure limitations. Conversely, traditional methods in Brunei Darussalam provide stability in religious understanding but fall short in fostering students' critical thinking and creativity skills. The study also found that educational policies and local cultures in both countries significantly influence the effectiveness of the applied teaching methods. These findings indicate that innovation in PAI teaching is necessary to address modern educational challenges but must still consider the stability offered by traditional methods.